2016
DOI: 10.1371/journal.pone.0168542
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics of a Citrullinated Pro-Filaggrin Epitope Recognized by Anti-Citrullinated Protein Antibodies in Rheumatoid Arthritis Sera

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease of complex etiology. A characteristic feature of a subset of RA is the presence of anti-citrullinated protein antibodies (ACPA), which correlate with a progressive disease course. In this study, we employed streptavidin capture enzyme-linked immunosorbent assay to analyze ACPA reactivity. Using the pro-filaggrin peptide HQCHQEST-Cit-GRSRGRCGRSGS, as template, we analyzed the reactivity of RA sera and healthy donor sera to various peptides in order to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 49 publications
(43 reference statements)
8
27
0
Order By: Relevance
“…Our data not only sustain conclusions obtained by others with citrullinated or noncitrullinated Ags (12,34,39,40) but also raised the question of which peptide characteristic had a major impact in the ELISA results. Indeed, only a few works have investigated the influence of the biotin position or the epitope-biotin distance, on single epitope recognition (11,34,40). With various peptides encompassing a single epitope in different conformations we showed that biotin-epitope distance was the major significant parameter that influenced epitope recognition.…”
Section: Discussionsupporting
confidence: 89%
“…Our data not only sustain conclusions obtained by others with citrullinated or noncitrullinated Ags (12,34,39,40) but also raised the question of which peptide characteristic had a major impact in the ELISA results. Indeed, only a few works have investigated the influence of the biotin position or the epitope-biotin distance, on single epitope recognition (11,34,40). With various peptides encompassing a single epitope in different conformations we showed that biotin-epitope distance was the major significant parameter that influenced epitope recognition.…”
Section: Discussionsupporting
confidence: 89%
“…Peptide 17, yielding the highest sensitivity, was only present in the EBV AG876 strain, whereas peptides 7 (P = 0.0020) and 8 (P = 0.0010) from the EBV GD1 and EBV B95-8 strains, respectively, yielded sensitivities of 60%. As seen, all three peptides contain repetitive Arg-Gly motifs, which previously have been reported for ACPA epitopes 8 , 10 , 27 , 28 , 30 .…”
Section: Resultssupporting
confidence: 81%
“…Highly significant reactivity was found to peptide 17 (P < 0.0001), which yielded a sensitivity of 93%. Interestingly, the two peptides, which were not recognised by the RA sera, contained no charged amino acids C-terminal to Cit, which previously has been reported to be essential for ACPA reactivity 13 , 28 , 29 . None of the HD sera reacted with the citrullinated peptides, which is illustrated by specificities of 100%.…”
Section: Resultsmentioning
confidence: 86%
“…By comparing the conformation of the 3 peptides bound to E4 in the crystals with their native forms (i.e., CII and α‐enolase), we found that they indeed undergo substantial conformational rearrangements upon binding to E4. The fact that the peptide conformation is essential for autoantibody reactivity is a finding that has been observed previously .…”
Section: Discussionsupporting
confidence: 65%